(untitled) (Journal of Social Sciences Review, 2023)
With the passage of time usage of social media has been enlarged. Hence, it has enhanced the risk of youth being bullied and has appeared such as a huge concern for parents, instructors as well as other working professionals remarkably. Objectives of this research was to identified the opinions of students about the presence, occurrence and exposure of cyber bullying behavior also the negative effects of cyberbullying on student’s thoughts and emotions. The sample consisted of 10 male students of five universities of Punjab in Pakistan. In this way qualitative research methods, semi-structured interview was conducted with each student who identify the individual opinions and behaviors. This type of qualitative research was a case study that was preferred the phenomena of cyber bullying. Content analysis was used to interpret the phenomena. As a result of this analysis, students on exhibited cyberbullying behaviors according to their individualities, their emotions of anger, sadness and hate were more often showed. The results of this research were reflected in the findings and suggestions persuaded for cyber victims. It was further recommended that psychological counselors should work in higher education institutions.